GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 93 species occurrences available in GBIF matching the query: TaxonKey: Oryza glumaepatula Steud. Country: Brazil. The dataset includes 93 records from 7 constituent datasets: 18 records from United States National Plant Germplasm System Collection. 47 records from The System-wide Information Network for Genetic Resources (SINGER). 16 records from SINGER Coordinator. 1 records from UB - Herbário da Universidade de Brasília. 1 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 7 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 3 records from CPAP - Herbário CPAP.
Keywords: GBIF; biodiversity; species occurrences